Do university entrance exams predict academic achievement? - Iida Häkkinen (Uppsala University, Department of Economics, 2004)
The study examines which factors predict academic performance at university and compares the predictive values of subject-related entrance exams and indicators of past school performance. The results show that in the fields of engineering and social sciences entrance exams predict both graduation and the number of study credits better than past performance. In education past school performance is a better predictor of graduation. Changing the admission rule to school grades would affect the average student performance negatively in engineering and social sciences but positively in education. Using only entrance exams would not significantly change the average performance in any field.
Keywords: I21; 330; University admission decisions; entrance exams; academic achievement; Studierende; Studium; Finnland